Toward a rural community vitality measurement practice. Issue 1 (1st January 2017) - Etuk, Lena E.; Acock, Alan
Abstract: Despite the increased interest among community development practitioners and the public in indicators of concepts like community vitality, resilience, or wellbeing, little research has been done to identify indicators that truly measure those concepts. In addition, there has been increased use of indices to describe social and economic conditions. This article uses a case to illuminate the methodological challenges of developing an index of community vitality and presents a possible practice solution. Factor analysis was piloted as a method that could be used to determine if a suite of 29 variables covering community capacity, social, economic, and environmental outcomes could be used as indicators of an underlying latent construct of community vitality. Use of this method in the case of Oregon counties and Siskiyou County, California, suggested that the variables capture a variety of community outcome dimensions, but do not correspond to a unitary concept of community vitality.